Peran Guru Dalam Mengimplementasikan Kegiatan Literasi Dalam Pembelajaran - Nofitaria; Arum Fitriana, Maulida; Hadi, Rusman (STAI AL-AMIN, 2025)
The purpose of this study is (1) to determine the role of teachers as facilitators in developing basic literacy activities for fourth-grade students at SDN 1 Mumbul Sari, (2) to determine the role of teachers as motivators in developing basic literacy activities for fourth-grade students at SDN 1 Mumbul Sari, (3) to determine the role of teachers as guides in improving reading and understanding skills for fourth-grade students at Mumbul Sari State Elementary School. This type of research is qualitative research with descriptive methods. This research was conducted at SDN 1 Mumbul Sari. The subjects of this study were the Principal and Fourth-grade Teachers. Data collection techniques were by means of interviews, observation, documentation. As well as data validity techniques were carried out by triangulation. The results of this study indicate that (1) the role of teachers as facilitators related to the use of various media used in literacy activities, involving students in managing the reading corner as a center for literacy activities by bringing books to fill the reading corner. Teachers also provide guidance by giving students the opportunity to ask questions, (2) As a motivator, the teacher provides appreciation in the implementation of literacy activities, holds competitions aimed at creating positive competition and literacy activities that involve cooperation between students such as the presence of a scientific supervisor whose job is to supervise the progress of literacy activities. The teacher as a teacher facilitator is able to guide students starting from recognizing letters, memorizing them until they have to write letters into a sentence. (3) The role of the teacher as a guide in improving the ability to read and understand texts of grade IV students of SDN 1 Mumbul Sari as a teacher sees the extent of the development of students' knowledge as well as students' attitudes and skills in the ability to read and understand texts. The teacher is able to improve skills in reading and understanding texts starting from recognizing letters, memorizing them until they have to write letters into a sentence and can be understood.